RANCANG BANGUN MODEL PINTU GARASI OTOMATIS MENGGUNAKAN SENSOR RFID - Budiharjo, Rahmat Satrio; Suryadi, Dedi; Suryono, Ahmad Fauzan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
The aim of this research is to develop a model of automatic home garage door using RFID sensor. Here, mechanical and control systems were designed. Mechanical systems were used 12V DC motors. Whereas, automatic control systems were carried out using PLC and Arduino UNO microcontrollers. Therefore, the desired speed and time can be controlled. Automatic garage doors worked with a drive system that is the influence of the distance to the distance and time generated during opening and vertical automatic doors. Theresult showed that automatic home garage door has been successfully developed.